A note on smooth forms on analytic spaces - Andersson, Mats; Samuelsson Kalm, Håkan (MATHEMATICA SCANDINAVICA, 2021)
We prove that any smooth mapping between reduced analytic spaces induces a natural pullback operation on smooth differential forms.